Follow-Up Ultrasound after Pyeloplasty should be Performed with An Empty Bladder: A Lesson from Monsieur Laplace - Ghirardo, Sergio; Diplomatico, Mario; Zancanaro, Matteo; Basso, Luca; Pennesi, Marco; Barbi, Egidio; Pederiva, Federica (Archives of Clinical and Biomedical Research, 2019)
Reason to report: Hydronephrosis caused by congenital ureteropelvic obstruction is quite common affecting up to 0.2% of infants and a pyeloplasty is the way to correct. Ultrasound is the technique of choice to follow up this kind of patient, but no other recommendations are present in literature. What was unique: So far no one has studied how the changing in the urinary way reflect the ultrasound image. We applied Laplace law to the geometric modelling of the urinary way of ten patients that underwent pyeloplasty before the age of three. Ramification of this report: After pyeloplasty, due to its reduced thickness, the pelvis presents a tendency to dilate, even by a low increase of urinary pressure. Ultrasound evaluation with an empty bladder can distinguish between an obstructive pattern and a reoccurrence of junctional occlusion.